Shake table test and numerical study of self‐centering steel frame with SMA braces - Qiu, Canxing; Zhu, Songye (Earthquake engineering & structural dynamics, 2017)
Summary Given their excellent self‐centering and energy‐dissipating capabilities, superelastic shape memory alloys (SMAs) become an emerging structural material in the field of earthquake engineering. This paper presents experimental and numerical studies on a scaled self‐centering steel frame with novel SMA braces (SMAB), which utilize superelastic Ni–Ti wires. The braces were fabricated and cyclically characterized before their installation in a two‐story one‐bay steel frame. The equivalent viscous damping ratio and ‘post‐yield’ stiffness ratio of the tested braces are around 5% and 0.15, respectively. In particular, the frame was seismically designed with nearly all pin connections, including the pinned column bases. To assess the seismic performance of the SMA braced frame (SMABF), a series of shake table tests were conducted, in which the SMABF was subjected to ground motions with incremental seismic intensity levels. No repair or replacement of structural members was performed during the entire series of tests. Experimental results showed that the SMAB could withstand several strong earthquakes with very limited capacity degradation. Thanks to the self‐centering capacity and pin‐connection design, the steel frame was subjected to limited damage and zero residual deformation even if the peak interstory drift ratio exceeded 2%. Good agreement was found between the experimental results and numerical simulations. The current study validates the prospect of using SMAB as a standalone seismic‐resisting component in critical building structures when high seismic performance or earthquake resilience is desirable under moderate and strong earthquakes. Copyright © 2016 John Wiley & Sons, Ltd.